Implementation of Multicultural Education Through Guidance and Counseling Services in Forming Student Character - Noperlis, Anggi Dwi; Firman, Firman; Bin Mohamed Sidik, Mohd Suhadi (Educational Guidance and Counseling Development Journal, 2024)
Multicultural education is a process of developing all human potential that respects plurality and heterogeneity as a consequence of cultural, ethnic, tribal and sectarian (religious) diversity. Character education is an embodiment of achieving a generation that is intelligent and capable of having morals and personality that are useful for the Indonesian nation which aims to create a young generation that has positive values. The aim of this research is to determine the application of multicultural education through guidance and counseling services in forming student character. This type of research is qualitative using a literature review. The results of the analysis show that the formation of adolescent character education through multicultural education is an important aspect in integrating learning in schools. One of them is that guidance and counseling services play a role in developing the character of teenagers through various service activities that can develop personal, social, learning and career aspects of teenagers optimally.